ASET BERWUJUD DAN KINERJA KEUANGAN UNIVERSITAS SWASTA DI KOTA PEKANBARU - Samsiah, Siti; Nik Muhammad, Nik Maheran; Rodiah, Siti (Jurnal Daya Saing, 2024)
The financial performance of private universities is a vital aspect in assessing the stability and operational sustainability of such higher education institutions. This study aims to analyze the relationship between tangible assets and financial performance of private universities. Tangible assets are measured using the dimensions of financial resources, physical facilities, and public facilities. While financial performance is measured using dimensions of self-financing capability, accountability, and asset management. The results showed that there is a positive relationship between tangible assets and financial performance in the context of private universities. Universities that have the availability of tangible assets that meet higher education standards tend to be able to show better financial performance. This shows the importance of tangible asset management in an effort to improve the financial performance of private universities.